I'dad Al-Mawad Al-Mula’imah Li Ta'lim Al-Lughah Al-Arabiyah - Nurlaila Nurlaila (Institut Agama Islam Negeri (IAIN) Metro, 2020)
An essential factor in the Arabic teaching process is learning materials. The teacher prepares the learning materials before entering the teaching process. Developing learning materials is considered one of the most challenging matters for the teacher because it is based on a set of basics and principles. So the learning materials should provide different types of information for learners, should be attractive to them that suit their preferences, should take into account their needs and the needs of society and should be related to their life. Therefore, the materials for Arabic teaching differ from stage to stage, from level to level, and from specialization to specialization according to the nature of learners and their characteristics. The teacher must prepare appropriate materials for learners to help them improve their motivation to learn Arabic.